2017
DOI: 10.1039/c7ra07948f
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot light-emitting diodes using a graphene oxide/PEDOT:PSS bilayer as hole injection layer

Abstract: Quantum dot (QD) light-emitting diode (QLED) displays are highly promising optoelectronic devices, but several critical issues remain to be solved. The hole-electron charge balance is particularly important but hole-injection is more difficult than electron-injection in QLEDs; as a result, good hole injection ability is required. Here, we introduce a graphene oxide (GO) layer between the anode electrode and a typical hole injection layer of poly(3,4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…2D materials are promising candidates to replace or modify PEDOT:PSS. In QLEDs, 2D materials have been introduced as HTL, HIL and dopant in composite HIL/HTL to enhance the performance of devices [58][59][60][61]. Figure 5 shows some related structures of QLED devices based on 2D materials.…”
Section: Two-dimensional Materials In Quantum Dot Light Emitting Diodmentioning
confidence: 99%
See 1 more Smart Citation
“…2D materials are promising candidates to replace or modify PEDOT:PSS. In QLEDs, 2D materials have been introduced as HTL, HIL and dopant in composite HIL/HTL to enhance the performance of devices [58][59][60][61]. Figure 5 shows some related structures of QLED devices based on 2D materials.…”
Section: Two-dimensional Materials In Quantum Dot Light Emitting Diodmentioning
confidence: 99%
“…Song inserted a GO HIL between ITO and PEDOT:PSS to improve the hole injection ability of QLED devices, as shown in Figure 6c [59]. The QLED device with the GO HIL exhibited a maximum luminance of 6741 cd/m 2 , CE of 1.34 cd/A and EQE of 1.61, which are 282%, 60% and 39% higher than those of the control device without GO HIL.…”
Section: Two-dimensional Materials In Quantum Dot Light Emitting Diodmentioning
confidence: 99%
“…PEDOT:PSS, a common hole injection layer (HIL), has a high electrical conductivity, high optical transparency, and smooth morphology, but it is highly acidic, which can cause erosion of the anode (indium‐tin‐oxide: ITO), resulting in reduced lifetime of QLED devices . To overcome this issue, new hole injection materials such as graphene oxide (GO), and transition metal‐oxides have been intensively studied as an alternative HIL replacing PEDOT:PSS. Examples of typical transition metal‐oxides for HIL include vanadium oxide (V 2 O 5 ), nickel oxides (NiOx), molybdenum oxide (MoO 3 ), and tungsten oxide (WO 3 ) …”
Section: Introductionmentioning
confidence: 99%
“…GO is inexpensive and easy to use in solution processes, however, GO is an insulator, and as such, its hole injection ability decreases dramatically with increasing layer thickness . Recently, our group reported that the use of a GO/PEDOT:PSS hole injection bilayer can significantly improve the hole injection ability in QLED compared to pure GO HIL, in which the GO layer was as thin as possible (≈2 nm) and the surface coverage of GO was not perfect .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation